Leachate Conductivity and Seed Viability in Sal (Shorea robusta Gaertn F.) Forests of Doon Valley - Behera, Falguni; Singh, Ombir; Shishodia, Vikas (Indian Forester, 2017)
An investigation was carried out to evaluate the seed vigour by electrical conductivity and seed characters of five seed sources of Shorea robusta from Doon valley forest in the state of Uttarakhand. Variations were observed in seed vigour, germination, seed length and width of seeds of different seed sources of sal. Among five seed sources studied, the seeds of S. robusta of Lachhiwala region of Doon valley exhibited more seed germination with less electrical conductivity values. The study showed that germination of sal seeds could be estimated by measuring electrical conductivity of seed leachates.